Preparation and Evaluation of Herbal Mouthwash Containing Hydroalcoholic Extract of Pongamia pinnata - Chaudhary, Preeti; Sharma, Raghavdeep; Rupanar, Sayali; Jadhav, Shweta; Bongade, Atharva; Shinde, Priyanka; Gavit, Snehal (Asian Journal of Biological and Life Sciences)
Aim: To formulate and evaluate an herbal mouthwash containing hydroalcoholic extract of Pongamia pinnata. The oval shaped oral cavity contains surfaces covered with bacteria such as Streptococcus mutans, Porphyromonas gingivalis, Staphylococcus and Lactobacillus that causes various tooth problems such as decay, gingivitis, sensitive teeth, root infection, bad breath and enamel erosions. The role of herbal plants is significant in the development of many oral formulations. Materials and Methods: Phytochemical screening of the above-mentioned plant was done. Leaf extraction was carried out for preparation of mouthwash. Formulation and evaluation of all three formulations was done. Results: Preliminary phytochemical screening of hydroalcoholic leaves extract of Pongamia pinnata confirmed the presence of phenolic compounds, tannins, flavonoids, terpenoids and alkaloids. Three formulations of mouthwash were prepared by using Pongamia pinnata, mint oil, PEG 40, glycerol, benzoic acid etc. and evaluated for different parameters like colour, odour, pH, viscosity, turbidity and stability studies. Conclusion: In comparison to chemical products, herbal drugs are widely regarded as highly effective. The goal of the present research was to formulate and evaluate an herbal mouthwash. So, in this research article we have focused on Pongamia pinnata (Common name Pongame oil tree) plant that belongs to Fabaceae family. Herbal mouthwashes can be used in combination with other oral hygiene practices like brushing and flossing. Due to their effectiveness against oral pathogens, herbal mouthwashes are high in demand because it provides immediate pain relief and has few side effects.
Keywords: Mint oil; Mouthwash; Oral hygiene; Pongamia pinnata; Streptococcus mutans